2019
DOI: 10.1002/phar.2208
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness Comparison of Ustekinumab, Infliximab, or Adalimumab for the Treatment of Moderate‐Severe Crohn's Disease in Biologic‐Naïve Patients

Abstract: Study ObjectiveUstekinumab was recently approved by the United States U.S. Food and Drug Administration for the treatment of Crohn's disease. In this analysis, we aimed to compare the cost‐effectiveness of ustekinumab, infliximab, or adalimumab for the treatment of moderate‐severe Crohn's disease in patients who failed conventional therapy (i.e., corticosteroids and immunomodulators) but were naïve to tumor necrosis factor antagonists (i.e., biologic drugs).DesignCost‐effectiveness analysis using a hybrid mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In addition to efficacy and safety, cost may be an important factor when selecting an appropriate first-line anti-TNF therapy. In some studies, ADA seems to be less costly than IFX; in others, the opposite seems to be true (65)(66)(67)(68). Moreover, biosimilars coming to the market have changed the scenario significantly (69,70).…”
Section: Adalimumab Vs Infliximabmentioning
confidence: 99%
“…In addition to efficacy and safety, cost may be an important factor when selecting an appropriate first-line anti-TNF therapy. In some studies, ADA seems to be less costly than IFX; in others, the opposite seems to be true (65)(66)(67)(68). Moreover, biosimilars coming to the market have changed the scenario significantly (69,70).…”
Section: Adalimumab Vs Infliximabmentioning
confidence: 99%
“…With lack of direct comparative or combination studies the choice of initial or subsequent therapies can be challenging. Anti-TNF therapy remains an important treatment option with the most clinical evidence and analysis of cost-effectiveness shows infliximab domination over both adalimumab and ustekinumab in terms of net monetary benefit [112]. The addition of selective JAK inhibition, targeted interleukin-23 blockage and potential bispecific antibodies are exciting prospective therapies for future clinical therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A USA-based investigation of the cost-effectiveness of infliximab, adalimumab, and ustekinumab in the management of moderate to severe CD reported that infliximab produced the most significant net monetary benefit with similar HRQoL outcomes 29 . In the United Kingdom, adalimumab was found to be associated with significantly lower costs than infliximab, a difference believed to be largely due to higher medication and administration costs 30 .…”
Section: Discussionmentioning
confidence: 99%